2016
DOI: 10.1016/j.toxrep.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

14-day toxicity studies of tetravalent and pentavalent vanadium compounds in Harlan Sprague Dawley rats and B6C3F1/N mice via drinking water exposure

Abstract: BackgroundThe National Toxicology Program (NTP) performed short-term toxicity studies of tetra- and pentavalent vanadium compounds, vanadyl sulfate and sodium metavanadate, respectively. Due to widespread human exposure and a lack of chronic toxicity data, there is concern for human health following oral exposure to soluble vanadium compounds.ObjectivesTo compare the potency and toxicological profile of vanadyl sulfate and sodium metavanadate using a short-term in vivo toxicity assay.MethodsAdult male and fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
4
13
0
Order By: Relevance
“…In the toxicity assay that was made in order to obtain working doses, mice presented diarrhea with MV of 15 and 20 mg/kg, these results agree with those reported by Llovet et al [ 19 ] and HSE [ 20 ] where MV caused intestinal, respiratory and nervous signs with both oral and intraperitoneal LD 50 (31 and 70 mg/kg respectively); in addition, Roberts et al [ 32 ] reported in Sprange Dawley, 18.1 mg/kg/day- and 16.1 mg/kg/day in B6C3F1/ mice, with lower doses compared with those use in this study, clinical manifestations such as: weight loss, ruffled coat, hunched posture, lethargy and abnormal gait. Therefore, 5 and 10 mg were chosen as working doses to continue with the experiments; with these doses, mice did not show clinical signs.…”
Section: Discussionsupporting
confidence: 88%
“…In the toxicity assay that was made in order to obtain working doses, mice presented diarrhea with MV of 15 and 20 mg/kg, these results agree with those reported by Llovet et al [ 19 ] and HSE [ 20 ] where MV caused intestinal, respiratory and nervous signs with both oral and intraperitoneal LD 50 (31 and 70 mg/kg respectively); in addition, Roberts et al [ 32 ] reported in Sprange Dawley, 18.1 mg/kg/day- and 16.1 mg/kg/day in B6C3F1/ mice, with lower doses compared with those use in this study, clinical manifestations such as: weight loss, ruffled coat, hunched posture, lethargy and abnormal gait. Therefore, 5 and 10 mg were chosen as working doses to continue with the experiments; with these doses, mice did not show clinical signs.…”
Section: Discussionsupporting
confidence: 88%
“…Excessive intake of vanadium is toxic for humans [9] and farm animals [10] with the effect dependent on the dose, duration of the exposure, and chemical form of V. Vanadium pentoxide (V 2 O 5 ) is the most toxic for human organisms, while the safest forms are vanadyl sulfate (VOSO 4 ) and metavanadate salts [11]. To date, the recommended daily allowance (RDA) for vanadium has not been determined [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased concentration of vanadium (5–10 mg/kg) reduces egg albumen quality (Wang et al., 2017). Vanadium compounds (sodium metavanadate) at elevated levels cause epididymis weight loss, sperm count loss in males, eye irritation and increases neoplastic cell growth (Llobet et al., 1993; Roberts et al., 2016).…”
Section: Introductionmentioning
confidence: 99%